Selective legal aspects of bank demand guarantees - Kelly-Louw, Michelle (University of South Africa, 2009)
Bank demand guarantees have become an established part of international trade. Demand guarantees, standby letters of credit and commercial letters of credit are all treated as autonomous contracts whose operation will not be interfered with by courts on grounds immaterial to the guarantee or credit itself. The idea in the documentary credit transaction/demand guarantee transaction is that if the documents (where applicable) presented are in line with the terms of the credit/guarantee the bank has to pay, and if the documents do not correspond to the requirements, the bank must not pay. However, over the years a limited number of exceptions to the autonomy principle of demand guarantees and letters of credit have come to be acknowledged and accepted in practice. In certain circumstances, the autonomy of demand guarantees and letters of credit may be ignored by the bank and regard may be had to the terms and conditions of the underlying contract. The main exceptions concern fraud and illegality in the underlying contract. In this thesis a great deal of consideration has been given to fraud and illegality as possible grounds on which payment under demand guarantees and letters of credit have been attacked (and sometimes even prevented) in the English, American and South African courts. It will be shown that the prospect of success depends on the law applicable to the demand guarantee and letter of credit, and the approach a court in a specific jurisdiction takes. At present, South Africa has limited literature on demand guarantees, and the case law regarding the grounds upon which payment under a demand guarantee might be prevented is scarce and often non-existent. In South Africa one finds guidance by looking at similar South African case law dealing with commercial and standby letters of credit and applying these similar principles to demand guarantees. The courts, furthermore, find guidance by looking at how other jurisdictions, in particular the English courts, deal with these issues. Therefore, how the South African courts currently deal/should be dealing/probably will be dealing with the unfair and fraudulent calling of demand guarantees/letters of credit is discussed in this thesis.
Keywords: Bank guarantee; Demand guarantee; Documentary credit; Fraud; Freezing injunction; Garantie bancaire; Letters of credit; Suretyship and guaranty

Lexique du droit des sûretés (common law) - Direction de la normalisation terminologique (Bulletin de terminologie, 2009)

Menkul kıymetleştirme ve varlığa dayalı menkul kıymetler - Turan, Gökçen (Ankara Üniversitesi, 2009)
Menkul kıymetleştirme düzenli nakit akışı sağlayan alacakların likit hale getirilmesi esasına dayanan bir finansman yöntemidir. Bu yöntemde, finansman ihtiyacı içinde olan şirket, düzenli nakit akışı sağlayan alacaklarını özel amaçlı kuruluşa devreder. Alacakları devralan özel amaçlı kuruluş, bu alacakları karşılık göstererek menkul kıymet ihraç eder. Menkul kıymeti satın alan yatırımcılara, vadesi geldiğinde anapara ve faiz ödemeleri, havuzdaki alacaklardan sağlanan gelirlerle yapılır. Böylece, alacakların ilk sahibi olan kaynak şirket, alacaklarının vadesini beklemeden nakit ihtiyacını gidermiş olurken, ihraç edilen menkul kıymeti satın alan yatırımcılar da, güvenilirliği yüksek ve şirketin risklerinden arındırılmış bir alacaklar topluluğunun güvencesi altında sağlam bir yatırım yapmış olurlar.5582 sayılı Kanunun temelinde de, menkul kıymetleştirme yöntemi kullanılarak, konut finansmanı sisteminin ikincil piyasa ayağını oluşturma düşüncesi vardır. Bu kapsamda, ipotekli konut kredilerinin menkul kıymetleştirilmesi sonucunda ihraç edilecek ipotek teminatlı menkul kıymetler ve ipoteğe dayalı menkul kıymetler düzenlenmiştir. İpotek teminatlı menkul kıymetler bir bilanço içi menkul kıymetleştirme özelliği gösterirken, ipoteğe dayalı menkul kıymetler bilanço dışı menkul kıymetleştirme niteliğine sahiptir. Her iki menkul kıymet türünde de, menkul kıymet sahiplerinin korunmasına azami şekilde özen gösterilmiş ve her durumda menkul kıymet sahiplerinin alacaklarını almalarına öncelik verilmiştir. İflasın teminat varlıklara menfi bir etkisinin olması her iki menkul kıymet türünde kanun hükmüyle engellenmiş, gerek teminat havuzu gerek fon portföyü dokunulmaz bir statüye kavuşturulmuştur.Aynı Kanunda, varlık teminatlı menkul kıymetler ve varlığa dayalı menkul kıymetler yoluyla, ipotekli konut kredileri dışındaki alacak çeşitlerinin de menkul kıymetleştirilmesi kabul edilmiştir.Sonuç olarak, menkul kıymetleştirme günümüzün vazgeçilmez finansman metotlarından biridir. Ancak menkul kıymetleştirmeden beklenen faydaların sağlanabilmesi, ana prensiplerine riayet edilerek uygulanmasına bağlıdır. Securitization is a method based on liquidation of receivables enabling regular cash flow. In this method, the company in need of financing transfers such receivables to special purpose vehicle. The special purpose vehicle which take over the receivables issues securities by assuring them. On due the capital and interest payments to the investors purchasing securities are made by the income acquired from the receivables in pool. Therefore, while the company, the originator of receivables, solve the problem of liquidity without waiting for the receivables?s due, the investors make a safe invesment under the assurance of a community of receivables that is highly secure and free of credit risk.On the basis of the Law 5582, there?s also the idea of forming the secondary part of housing finance system by using securitization method. Within this framework, mortgage covered bonds and mortgage backed securities have been regulated, both of which are issued as a result of securitization of residential mortgage loans. Mortgage covered bonds display a characteristic of on-balance sheet, while mortgage backed securities have off-balance sheet property.In both types of securities, utmost great pains to protect securities owners is taken and that securities owners are satisfied under any circumstances is of high priority. Bankruptcy?s negative effect on cover assets is impeded with a law article, thus both cover pool and fund portfolio acquire an immune statute.In the same Law, other types of receivables except residential mortgage loans might be securitised is acknowledged through asset covered bonds and asset backed securities.Consequently, today, securitization is one of indispensible way of financing. However, that expected benefits from securitization can be obtained is possible provided that it is performed with respect to main principles.
Keywords: Asset backed bonds; Asset-backed securitization; Commercial law; Financing; Financing methods; Finansman; Finansman yöntemleri; Menkul kıymetleştirme; Ticaret hukuku; Turkish Law; Türk Hukuku; Varlığa dayalı menkul kıymetler